2015
DOI: 10.17265/1934-7359/2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Feasibility of Achieving Level 2 Building Information Modeling by 2016 in the UK

Abstract: Abstract:The aim of this study is to investigate the current status and feasibility of achieving Level 2 BIM (building information modeling) usage that is to be made mandatory by the UK government on its projects by the year 2016. This study assesses the level at which organizational and practitioner knowledge of BIM is currently positioned. The UK government, being the largest public stakeholder client, has realized the benefits and advantages of BIM when used in procuring projects across their lifecycle in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Based on ISO 19650-1:2018, BIM is "a digital representation of physical and functional characteristics of a facility which forms a reliable basis for decisions during its life-cycle; defined as existing from earliest conception to demolition". The BIM process (Figure 1), which has evolved over the years, is mandatory for the contractors (BIM Level 2) that receive public tenders in the UK since 2016 (Ganah & John, 2015). This government decision has increased the interest in BIM in the private sector and across the AEC industry (Infrastructure and Projects Authority, 2016).…”
Section: Review Of Existing Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on ISO 19650-1:2018, BIM is "a digital representation of physical and functional characteristics of a facility which forms a reliable basis for decisions during its life-cycle; defined as existing from earliest conception to demolition". The BIM process (Figure 1), which has evolved over the years, is mandatory for the contractors (BIM Level 2) that receive public tenders in the UK since 2016 (Ganah & John, 2015). This government decision has increased the interest in BIM in the private sector and across the AEC industry (Infrastructure and Projects Authority, 2016).…”
Section: Review Of Existing Workmentioning
confidence: 99%
“…This commitment set out in the government's 2011 building strategy, is one of the decisions taken as part of the UK government's work process to reduce the cost of state building projects by 15-20% (Cabinet Office, 2011). (Ganah & John, 2015) In the AEC industry, the dominant data collection techniques are Light Detection and Ranging (LiDAR), also known as Laser Detection and Ranging (LADAR), or 3D laser scanning, photogrammetry and videogrammetry systems, as opposed to other methods such as Radio Frequency Identification (RFID) and barcode tagging (Tang et al, 2022;Sadeghineko & Kumar, 2020b). The 3D laser scanning methodology produces a collection of 3D point measurements commonly referred to as point cloud data (PCD).…”
Section: Review Of Existing Workmentioning
confidence: 99%
“…He suggested that the use of BIM should be made mandatory by the state. Ganah and John [46] stated that all types of contractors in the construction industry are lagging behind in adopting new generation technologies. Sun [47] emphasized that one of the important factors limiting BIM applications in the construction industry is the lack of qualified personnel who are familiar with BIM and have experience in using BIM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The heavy workload of project designers [25,33] Lack of academic information and pilot studies, shortcomings in promotion [26,[34][35][36]51,58,59] Lack of sufficient input data to create a BIM model [37] Lack of theoretical and practical practice of BIM tools [52] Lack of secure infrastructure in BIM models [38,53,54] Deficiencies in regulations, directives, and specifications about BIM [34,56] Lack of sufficient standards and guidelines about BIM [57] Insufficient internet infrastructure or open electronic data-sharing platforms [38,53,55] Lack of motivation on use of BIM by employers, owners, project managers [26,34,36,39,40,59] Lack of knowledge regarding legal issues attributed to BIM-based projects and contacts [41][42][43][44]58] Resistance to new generation technologies and changes [45,46] Lack of qualified staff [34,47,57] Necessity of extra budgeting for the use of BIM technologies and personnel training [28,34,59] Lack of information on BIM-based organizational scheme and project management [40,49] Time constraints …”
Section: Barriers Referencesmentioning
confidence: 99%
“…An example can be the neglect of a building during its maintenance. Inefficiently spent operating resources will cause an impact on the operation of internal technical equipment, loss of warranties and a dramatic impact on operating costs (Ganah 2015). However, errors made at different stages of a construction project will also have different impacts on life cycle costs.…”
Section: Introductionmentioning
confidence: 99%